An Exploration of Instructional Support Use in a Secondary Science Classroom - Tyler, Doris Kennedy (Journal of the American Academy of Special Education Professionals, 2011)
Our classrooms are becoming more diverse; with this diversity educators need to find multiple strategies to address the varied learning preferences in their classrooms. By the time students enter secondary education, the expectation is that they are capable of reading and organizing information from a text. However, all of our students do not come to a high school course prepared with the essential skills to benefit from instruction. This can be especially true with content such as science. This study explores the use of varied instructional supports to facilitate better access to the curriculum for diverse learners, especially those with special needs. Students were provided text materials, podcasts, and digital books. Surveys indicated that students used the text based materials most frequently.